1986
DOI: 10.1007/bf00251975
|View full text |Cite
|
Sign up to set email alerts
|

Automated determination of the right ventricular ejection fraction by digital processing of 81mKr scintigrams

Abstract: A method is presented for the automated determination of the right ventricular ejection fraction (RVEF) by digital image processing of scintigrams obtained by intravenous infusion of Krypton 81m (81mKr) dissolved in a glucose solution. End-diastolic and end-systolic sum pictures were computed by the addition of approximately 30-40 frames selected from the time-activity curve of a preliminary, manually drawn, right ventricular region of interest. After processing these two images with an adaptive Wiener filter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Bourguignon et al [7] calculated the RVEF using equilibrium images of Tc 99m and reported correlation of 0.88 between the automatic and the manual approach. Elfner et al [8] used a Kr 81m infusion technique that depended partially on manual operations such as an operator defined region of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Bourguignon et al [7] calculated the RVEF using equilibrium images of Tc 99m and reported correlation of 0.88 between the automatic and the manual approach. Elfner et al [8] used a Kr 81m infusion technique that depended partially on manual operations such as an operator defined region of interest.…”
Section: Introductionmentioning
confidence: 99%